(untitled) (Journal of the College of Basic Education, 2022)
Writing about Al-Ghazali or Ibn Rushd may be seen as writing on a topic that is more like a consumerIt will not come up with anything new after the large amount of research, letters and books that dealt with them in research and analysis. However, this view - in fact - overlooks the fact that scientific research is an ongoing research that does not stop at an endAs long as the cognitive mind is a diligent mind, it always searches for something new or for illuminating points that have not been highlightedAs much as you deserve or what you intubate. The subject of interpretation for both Al-Ghazali and Ibn Rushd can be said to be one of the proofs of this fact. He isA research that internalizes a set of facts that are important in the final position of these two sciences, foremost of which is that they areThey are almost identical in the law of interpretation; It is a fact before completing this research, it was a hypothesis for the researcher afterhis knowledge of their texts on this subject; And the